Career Services and Industrial Arts. Materials Catalogue - Stovall, Ruth.; Alabama State Dept. of Education, Montgomery. Div. of Vocational Education and Community Colleges ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
The catalogue annotates all materials which are available for loan from the Career Services and Industrial Arts Instructional Materials Laboratory in the Vocational Education and Community Colleges Division of the Alabama State Department of Education. Section 1 annotates listings for over 200 books, on career education and career guidance. Section 2 lists 69 titles of books contained in two series of works designed to describe all the major career options open to young people. Section 3 lists for grades 1-12 several hundred units of study in careers for the various subject fields developed by teachers in Alabama and Cobb County, Georgia. Section 4 cites nearly 100 books which cover the various industrial arts subjects. Section 5 lists three special need books and one series of 45 academic skills titles. Section 6 cites approximately 70 position papers and monographs which deal with various aspects of career education. Section 7 lists 11 career education journals. Section 8 describes 15 career films and one series of 44 films on specific occupations. Section 9 lists approximately 40 career filmstrips. Section 10 describes 32 multi-media kits, and section 11 describes five slide kits. (JR)
Sponsoring Agency: Bureau of Occupational and Adult Education (DHEW/OE), Washington, DC.
Sponsoring Agency: Missouri Univ., Columbia. Career Guidance Counseling Placement Project.
Contract Number: OEG-71-4663.
Educational level discussed: Early Childhood Education.
Educational level discussed: Elementary Secondary Education.
Educational level discussed: Postsecondary Education.
Keywords: Annotated Bibliographies; Audiovisual Aids; Career Awareness; Career Education; Career Guidance; Catalogs; Early Childhood Education; Elementary Secondary Education; Industrial Arts; Instructional Materials; Postsecondary Education; Teacher Developed Materials; Unit Plan; Vocational Education; Alabama; Reference Materials, Bibliographies